Rational Emotive Behavior Therapy (REBT) Counseling to Increase Students Learning Motivation - Fatimah Intan Nur’aini; Awik Hidayati Hidayati; Aldila Fitri Radite Nur Maynawati (Pamomong: Journal of Islamic Educational Counseling, 2022)
This study aimed to determine the effect of Rational Emotive Behavior Therapy (REBT) counseling on increasing the learning motivation of junior high school students in Jetak Hamlet, Purwantoro District, Wonogiri Regency. The existence of this research was to encourage students to learn during the online learning period. This experimental research used a quantitative method and a Quasi-Experimental Design with One Group Pretest-Posttest pattern. The population was all junior high school students domiciled in Jetak Hamlet, while the sample was junior high school students in Jetak with low learning motivation based on the pretest results. The data collection method used a psychological scale, namely the learning motivation scale. The results showed an increased learning motivation in the three students with low learning motivation. The pretest of learning motivation got an average percentage of 46.26% (low), and the posttest got an average percentage of 67.97% (medium). In the hypothesis tested through the Wilcoxon Signed Rank Test results, the Zscore was -1.604 Ztable 0.0495 with a significance level of 5% and a significant asymptotic of 0.109. Thus, Ha is rejected, and H0 is accepted. So, it can be concluded that Rational Emotive Behavior Therapy (REBT) counseling has a significant effect on increasing the learning motivation of junior high school students in Jetak Hamlet, Purwantoro District, Wonogiri Regency.